ANALISIS PENGGUNAAN IIKAE ATAU PARAFRASE DALAM PERCAKAPAN BAHASA JEPANG - Romando, Rio Rizki (Universitas Negeri Semarang, 2017)
This research is aiming to find out the types, how to convey, and paraphrase’s purposes or in Japanese is iikae. Paraphrase in Japanese communication is the fundamental aspect for the Japanese language learners. However, in the communication, there are still many problems, for example, vocabulary knowledge limit and grammar knowledge. Although, there are still many problems, it could be overcome with paraphrase or iikae in Japanese. The data source of this research is TV Show Ameejipangu which is broadcasted on TBS channel or can be downloaded on YouTube. Data were collected by watch and note method on the sentences which consist of iikae or paraphrase from foreigner to Japanese. The results of this research are four types iikae or paraphrases. There are definitive paraphrase, suironteki iikae (parphrase based on conclusion), synonym paraphrase, and explicative paraphrase. Thence, how to convey iikae with gairaigo (foreign origin words), gesture, and periphrase. Finally, iikae’s purposes are to give a general image to listener, giving prominent, to make the sentence shorter, etc.